2012
DOI: 10.1093/hmg/dds348
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X premutation RNA is sufficient to cause primary ovarian insufficiency in mice

Abstract: Spontaneous 46,XX primary ovarian insufficiency (POI), also known as 'premature menopause' or 'premature ovarian failure', refers to ovarian dysfunction that results in a range of abnormalities, from infertility to early menopause as the end stage. The most common known genetic cause of POI is the expansion of a CGG repeat to 55 -199 copies (premutation) in the 5 ′ untranslated region in the X-linked fragile X mental retardation 1 (FMR1) gene. POI associated with the FMR1 premutation is referred to as fragile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 36 publications
6
90
2
2
Order By: Relevance
“…Similarly, FMRP expression was described in mouse female fetal primordial cells and also in follicular cells in the adult (Bakker et al 2000). Recent works by Hoffman et al (2012) and Lu et al (2012) described expression of FMRP in murine granulosa and luteal cells as well as in the oocyte. In addition, FMRP expression in ovaries from women of different ages has also been described, mainly in the oocyte and GCs (Schuettler et al 2011, Willemsen et al 2011.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Similarly, FMRP expression was described in mouse female fetal primordial cells and also in follicular cells in the adult (Bakker et al 2000). Recent works by Hoffman et al (2012) and Lu et al (2012) described expression of FMRP in murine granulosa and luteal cells as well as in the oocyte. In addition, FMRP expression in ovaries from women of different ages has also been described, mainly in the oocyte and GCs (Schuettler et al 2011, Willemsen et al 2011.…”
Section: Discussionmentioning
confidence: 60%
“…Histological analysis in a knock-in model with 130 CGG repeats revealed ovarian abnormalities (Hoffman et al 2012). In addition, the characterization of a transgenic mouse carrying a premutation of 90 CGG repeats showed that premutated RNA impaired female fertility, reduced the number of growing follicles and altered selective serum hormone levels, thus resembling FXPOI in humans (Lu et al 2012). Given the advanced technologies in transgenic and knock-in models in rat, and taking into account the data presented in our work, it would be an interesting challenge to develop a rat model of FXPOI to further contribute to the better understanding of the influence of FMR1 CGG repeats in ovarian pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…By consequence, the mRNA levels build-up in the cells where it is hypothesized to exert cytotoxic effects (RNA/protein toxic gain-of-function disorder). Human FMR1 mRNA in transgenic mice prompts premature ovarian insufficiency (POI) [60]. In this animal model, the FMR1 premutation does not play any role in early primordial follicles, but seems to act on subsequent steps of follicular maturation, as well as increasing the degree of follicular apoptosis.…”
Section: How Fmr1 Mutations Influence Different Phenotypesmentioning
confidence: 89%
“…FXPOI involves infertility, irregular menses and an early menopause. Although in theory, FXPOI could arise from the presence of a smaller than normal primordial follicle pool at birth, insights from two different publications using a knock-in mouse model, demonstrated that FXPOI is due to an accelerated loss or an impaired development of the growing follicles (Hoffman et al, 2012;Lu et al, 2012). Regarding the FMR1 CGG repeat number, it has also been described that normal alleles containing lower CGG repeat expansions (b 26 CGGs) are associated with a polycystic ovarian-like phenotype that would lead to a prematurely diminished functional ovarian reserve (Gleicher et al, 2010(Gleicher et al, , 2013.…”
Section: Discussionmentioning
confidence: 99%